HKUST‐1 Membranes Anchored on Porous Substrate by Hetero MIL‐110 Nanorod Array Seeds. Issue 36 (29th July 2013) - Mao, Yiyin; Cao, Wei; Li, Junwei; Sun, Luwei; Peng, Xinsheng
<x xml:space="preserve">Abstract</x> Great anchors and seeds: Hetero‐seeding growth processes and anchored nanorod arrays were successfully utilized in the synthesis of HKUST‐1 membranes. These arrays were firmly anchored on porous substrates by using a MIL‐110 nanorod array as both the anchor and seed (see scheme). The resulting HKUST‐1 membranes demonstrated good separation factors for binary gases exceeding the Knudson selectivity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>